Neighborhood Structural Factors and Proximal Risk for Youth Substance Use - Cambron, Christopher; Kosterman, Rick; Rhew, Isaac C.; Catalano, Richard F.; Guttmannova, Katarina; Hawkins, J. David (Prevention Science, 2020)
This study examined associations of neighborhood structural factors (census-based measures, socioeconomic disadvantage, and residential stability); self-reported measures of general and substance use-specific risk factors across neighborhood, school, peer, and family domains; and sociodemographic factors with substance use among 9th grade students. Data drawn from the Seattle Social Development Project, a theory-driven longitudinal study originating in Seattle, WA, were used to estimate associations between risk factors and past month cigarette smoking, binge drinking, marijuana use, and polysubstance use among students (N = 766). Results of logistic regression models adjusting for neighborhood clustering and including all domains of risk factors simultaneously indicated that neighborhood socioeconomic disadvantage was associated with a significantly higher likelihood of cigarette smoking, binge drinking, and polysubstance use, but not marijuana use. In fully controlled models, substance use-specific risk factors across neighborhood, school, peer, and family domains were also associated with increased likelihood of substance use and results differed by the outcome considered. Results highlight substance-specific risk factors as an intervention target for reducing youth substance use and suggest that further research is needed examining mechanisms linking neighborhood socioeconomic disadvantage and youth substance use.